Phenolic compounds of Galega Vulgar and Cobrançosa olive oils along early ripening stages - Peres, Fátima (2016)
In this study, the lipophilic and hydrophilic phenol composition of virgin olive oils (VOO) obtained from olives from two of the most important Portuguese cultivars (‘Galega Vulgar’ and ‘Cobrançosa’), harvested at different ripening stages and under two irrigation schemes (rain fed and irrigated), was evaluated. Phenolic alcohols (hydroxytyrosol and tyrosol), phenolic acids and derivatives and flavonoids (luteolin and apigenin), as well as tocopherols were quantified. Lipophilic (>300 mg kg 1) and hydrophilic phenols (>600 mg kg 1) were present in high contents in both VOO, for early ripening stages. Gamma-tocopherol content is higher in ‘Galega Vulgar’ VOO. Total phenols showed a decrease between ripening index 2.5 and 3.5. The dialdehydic form of elenolic acid linked to hydroxytyrosol (3,4-DHPEA-EDA), also known as oleacein, was the major phenolic compound identified in both oils. The concentration of free hydroxytyrosol and tyrosol in both VOO is very low while their esterified derivatives, like 3,4-DHPEA-EDA and p- HPEA-EDA, are much more abundant